Soft x-ray yield from NX2 plasma focus - Lee, S.; Rawat, R. S.; Lee, P.; Saw, S. H. (AIP Publishing LLC, 2009)
The Lee model code is used to compute neon soft x-ray yield Ysxr for the NX2 plasma focus as a function of pressure. Comparison with measured Ysxr shows reasonable agreement in the Ysxr versus pressure curve, the absolute maximum yield as well as the optimum pressure. This gives confidence that the code gives a good representation of the neon plasma focus in terms of gross properties including speeds and trajectories and soft x-ray yields, despite its lack of modeling localized regions of higher densities and temperatures. Computed current curves versus pressure are presented and discussed particularly in terms of the dynamic resistance of the axial phase. Computed gross properties of the plasma focus including peak discharge current Ipeak, pinch current Ipinch, minimum pinch radius rmin, plasma density at the middle duration of pinch npinch, and plasma temperature at middle duration of pinch Tpinch are presented and the trends in variation of these are discussed to explain the peaking of Ysxr at optimum pressure.